Prevalence of toxic, compression-ischemic, diabetic and atherosclerotic polyneuropathy in teleuts - primary population of Kemerovo region - A. V. Osipov; A. V. Kolbasko; A. G. Chechenin; A. L. Onishchenko (Acta Biomedica Scientifica, 2013)
In the study carried out in primary population of Kemerovo region - teleuts - we determined the prevalence of toxic, compression-ischemic (tunnel), diabetic and atherosclerotic polyneuropathy. It was determined that the frequency of these diseases is different depending on the sex, age, social status, profession, and place of residence. In male population toxic polyneuropathy prevails in age groups of 30-39 and. 40-49 years. Compression-ischemic polyneuropathy prevailed in women of 50-59 years who belonged to the unemployment and. employees social groups. Diabetic and. atherosclerotic polyneuropathy has the most prevalence in women of 70 years and. older in the social group of pensioners.